1999
DOI: 10.1111/j.1469-445x.1999.01857.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thyrotrophin‐Releasing Hormone on Thermoregulatory Adaptation after Birth in Near‐Term Lambs Delivered by Caesarean Section

Abstract: We investigated the hypothesis that exogenous stimulation with thyrotrophin-releasing hormone (TRH) immediately prior to umbilical cord clamping can improve thermoregulatory adaptation after birth in near-term lambs delivered by Caesarean section. Lambs received an umbilical vein injection of saline +/- TRH (8 microg) prior to cord clamping. The rate of change in colonic temperature and oxygen consumption after birth were not influenced by TRH, but TRH-treated lambs exhibited a greater incidence of shivering c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In the hypothalamus-pituitarythyroid axis, the cold-induced increase in TRH stimulates TSH secretion by the pituitary, which in turn stimulates thyroid hormone release from the thyroid (11). Research in various species showed that both core body temperature (32,33) and BAT-specific temperature (13) are increased by central or peripheral administration of TRH. Intracerebroventricular infusion of TRH in rodents was found to activate BAT via sympathetic neurons, an effect that could be blocked by pre-treatment with TRHreceptor type 1 antibodies and attenuated by sympathetic denervation of BAT depots (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hypothalamus-pituitarythyroid axis, the cold-induced increase in TRH stimulates TSH secretion by the pituitary, which in turn stimulates thyroid hormone release from the thyroid (11). Research in various species showed that both core body temperature (32,33) and BAT-specific temperature (13) are increased by central or peripheral administration of TRH. Intracerebroventricular infusion of TRH in rodents was found to activate BAT via sympathetic neurons, an effect that could be blocked by pre-treatment with TRHreceptor type 1 antibodies and attenuated by sympathetic denervation of BAT depots (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TRHknockout mice show cold intolerance (12). Interestingly, both central and peripheral administration of TRH was found to increase BAT thermogenesis in several mammals (13,14). Whether peripheral administration of TRH has similar effects in humans is unknown.…”
Section: Introductionmentioning
confidence: 99%